Pengaruh Sistem Pengendalian Internal Terhadap Pencapaian Good Government Governance Melalui Pencegahan dan Pengungkapan Fraud - Yasmi Nurdin; Fahriah Tahar; Nurbayani Nurbayani (Jurnal Akuntansi dan Pajak, 2019)
This study examines the extent of perception of government’s internal auditors (BPKP) in assessing the ability of the government's internal control system (SPIP) to detect and prevent fraud and encouraging the achievement of Good Government Governance (GGG) in the government agencies. Using the survey method to BPKP auditors at the South Sulawesi representative office and the PLS approach as a statistical tool, empirical facts were found, SPIP had a significant effect on the fraud prevention, fraud disclosure, and achievement of GGG. Moreover, Fraud Control Plan (FCP) also has a significant influence on the achievement of GGG. These results indicate the importance of periodically evaluating the effectiveness of SPIP and FCP by BPKP, in order to doing further improvement of these systems for reaching the GGG.